Stay just a little bit longer: A scoping review of foster parent engagement in the U.S. (March 2023) - Williams, Kimberly A.; Lewis, Ericka M.; Feely, Megan
Highlights: Training alone is not enough to encourage foster parent engagement. Foster parents require support from personal, peer, and professional sources. Strategies to increase retention should be holistic yet targeted. Abstract: Despite the growing need for quality foster homes, retaining foster parents continues to be a challenge. A significant burden is placed on child welfare agencies to recruit, train, and retain quality foster parents to ensure available homes for children in need. To synthesize what is known about foster parent engagement, this article describes the modifiable factors impacting foster parent satisfaction, commitment, and retention. This scoping review engaged in a comprehensive exploration of the literature by mapping out the extent, range, and nature of foster parent engagement, screening studies based on inclusion and exclusion criteria, and summarizing findings. Twenty-three articles met inclusion criteria. Three themes emerged as factors impacting foster parent engagement: (1) training, (2) resources, and (3) relationships. Eight studies evaluated unspecified training and three studies examined evidenced-informed training interventions. Resources were explored in ten studies and included concrete resources such as respite, financial assistance, and transportation. Relationships, categorized as professional social support (n = 15) and personal social support (n = 16), were also studied. A notable finding of this scoping review is the importance of relationship building across foster care stakeholders. Specifically, strengthened relationships between foster parents and caseworkers improved outcomes across all components of foster care engagement (satisfaction, commitment, and retention). Further studies are needed to understand the ways in which specialized training and social support improve foster parent engagement over time.